Pengaruh Kepemimpinan dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada Metro Komputer Bandar Lampung - Hasanah, Rizkiyah; Putri Maharani, Nabila (Jambura Economic Education Journal, 2025)
This study was conducted at Metro Komputer Bandar Lampung to examine the extent to which leadership and work environment influence employee performance effectiveness. The research employed a quantitative method, with data collected through questionnaires. The findings demonstrate that leadership has a significant influence on driving productivity. Meanwhile, the work environment also positively impacts work efficiency. Further statistical analysis reveals that the work environment tends to have a greater influence than leadership. Factors such as facility availability, strong interpersonal relationships, and comfortable working conditions contribute to boosting employee morale and work outcomes. Therefore, the strategic recommendation for the company is to optimize visionary leadership while fostering an ergonomic and collaborative work environment to achieve better business objectives.